International Experience in Bus Rapid Transit Implementation : Synthesis of Lessons Learned from Lagos, Johannesburg, Jakarta, Delhi, and Ahmedabad - Kumar, Ajay; Zimmerman, Samuel; Agarwal, O.P. (World Bank, Washington, DC, 2013)
It is in this context that this study has been undertaken to document BRT case studies in terms of the political setting, institutions/governance, public involvement and communications, service/operations/management and planning and their relationship to investment performance. The study has been undertaken in recognition of the fact that successful implementation and operation of BRT systems often reflects non-physical actors like leadership, communications, organizational structure, service planning and operating practices rather than the design of transitways, stations, terminals and vehicles. This paper does not seek to compare BRT with other forms of public transport but only seeks to evaluate a sample of BRT systems in terms of the softer issues that have contributed making a BRT system successful or not so successful.